2020
DOI: 10.3390/nu12061588
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of Hydrangea serrata (Thunb.) Ser. Leaves Extract Improves Wrinkles, Hydration, Elasticity, Texture, and Roughness in Human Skin: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Previously, we reported that the hot water extract of Hydrangea serrata leaves (WHS) and its active component, hydrangenol, possess in vitro and in vivo effects on skin wrinkles and moisturization. We conducted a randomized, double-blind, placebo-controlled trial to clinically evaluate the effect of WHS on human skin. Participants (n = 151) were randomly assigned to receive either WHS 300 mg, WHS 600 mg, or placebo, once daily for 12 weeks. Skin wrinkle, hydration, elasticity, texture, and roughness parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…Makino have been shown to possess anti-obesity effects. 36,43 In particular, we have reported the anti-photoaging effects of EEB via the MAPK/AP-1, Smad, and ROS-mediated Nrf2 pathways. 30 Since the anti-obesity effects of E. bicyclis have not been revealed to date, in this study, we evaluated the anti-obesity efficacy and revealed the molecular mechanism of EEB in differentiated 3T3-L1 preadipocytes and an HFD-induced C57BL/6 mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Makino have been shown to possess anti-obesity effects. 36,43 In particular, we have reported the anti-photoaging effects of EEB via the MAPK/AP-1, Smad, and ROS-mediated Nrf2 pathways. 30 Since the anti-obesity effects of E. bicyclis have not been revealed to date, in this study, we evaluated the anti-obesity efficacy and revealed the molecular mechanism of EEB in differentiated 3T3-L1 preadipocytes and an HFD-induced C57BL/6 mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of skin elasticity and roughness was performed with minor modification to the methods described in previous studies [ 20 , 21 ]. Skin elasticity was measured using a Cutometer MPA 580 (Courage and Khazaka Electronics), which works by suctioning the skin into an aperture using a probe with 450 mbar negative pressure.…”
Section: Methodsmentioning
confidence: 99%
“…A hot water extract from the leaves of H. serrata was prepared in the form of a tablet. Test tablets (600 mg WHS) and placebo tablets were prepared, as described previously [ 20 ]. The placebo tablets used in this study were indistinguishable from the test tablets.…”
Section: Methodsmentioning
confidence: 99%